Rebuilding Germany: The creation of the social market economy, 1945-1957 - Hook, James C Van (Cambridge University, 2013)
Rebuilding Germany examines the 1948 West German economic reforms that dismantled the Nazi command economy and ushered in the fabled "economic miracle" of the 1950s. Van Hook evaluates the U.S. role in German reconstruction, the problematic relationship of Chancellor Konrad Adenauer and his economics minister, Ludwig Erhard, the West German "economic miracle," and the extent to which the social market economy represented a departure from the German past. Van Hook evaluates the American role in West German recovery and the debates about economic policy within West Germany, to show that Germans themselves had surprising room to shape their economic and industrial system.